Validation of The Mathematical Knowledge For Teaching Statistics Instrument - Merci̇mek, Oktay; Erbaş, Ayhan Kürşat (Cumhuriyet University, 2017)
The purpose of this study is to assess preserviceteachers’ mathematical knowledge forteaching statistics (MKT-S) and identify the relationship between the components of this knowledge. For this purpose, MKT-S instrument consisting of two dimensions, ‘content knowledge’ (CK) and ‘pedagogical content knowledge’ (PCK) was developed, and applied to659 preservice middle school mathematics teachers (PTs). Confirmatory factor analysis showed that CK and PCK are two different dimensions of mathematical knowledge of teaching statistics. Third year and fourthyear preservice teachers’ factor scores were significantly different and fourth year preservice teachers’ factor scores were slightly higher. It was found that CK factor scores were highly correlated with PCK factor scores. The reliability levels were 0.65 for CK factor scores and 0.76 for PCK factor scores. MKT-S instrument developed in this study has several implications for teacher education. MKT-Sinstrument can be used to evaluate efficiency of PTs’ mathematical knowledge for teachingstatistics. Instrument can be adapted for in-service teachers.
Keywords: Pedagojik alan bilgisi; Pedagogical content knowledge; Item Response Theory; Alan bilgisi; Öğretmen bilgisi; Teacher knowledge; content knowledge; pedagogical content knowledge; teaching statistics; Item Response Theory; Confirmatory Factor Analysis.; İstatistik öğretimi; Teacher knowledge; Content knowledge; Madde Tepki Kuramı; Öğretmen Bilgisi; Pedagojik Alan Bilgisi; Alan Bilgisi; istatistik öğretimi; Madde Tepki Kuramı; Doğrulayıcı faktör analiz; Doğrulayıcı faktör analizi; Teaching statistics; Confirmatory Factor Analysis; 4. Education